INTERVENSI UNTUK MENURUNKAN NYERI POST SECTIO CAESAREA - PIPIH NAPISAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Post section caesarea can cause pain in the area of the abdominal incision wound. Post section caesarean pain needs correct and effective treatment so that it does not cause complications. The purpose of this article is to determine the effectiveness of various interventions that can reduce the pain scale of post section caesarea. Writing articles using literature studies. Search data using four databases, namely EBSCO, Proquest, Neliti and Google Scholar. Article criteria, namely in English and Indonesian, published in 2020-2021, research studies using randomized control trials and quasi experiments. Keywords in article search using interventions AND pain AND post section caesarea. The data needed is collected through text studies, then analyzed using JBI. Based on the results of the literature study, it shows that there are 19 articles. Single interventions, namely abdominal breathing relaxation techniques, lavender essential oil, acupuncture, guided imagery therapy, deep tissue massage, progressive muscle relaxation, benson relaxation exercises, distraction therapy listening to music, mediation of dhikr, lavender extract, foot massage, and gel package. Meanwhile, the combination interventions, namely lavender oil and oxygen, lemon and mozart classical music therapy, swedish massage and lemon aromatherapy, deep breathing techniques, and music therapy. All studies proved effective for reducing the post SC pain scale. One of the interventions that are effective, easy to do independently by the mother at home, safe and do not cause side effects, are deep breathing relaxation techniques with abdominal breathing techniques, progressive muscle relaxation, Benson relaxation, dzikir mediation and guided imagery therapy. However, research is still limited both abroad and in Indonesia. ABSTRAKPost section caesarea dapat menimbulkan nyeri diarea luka insisi abdomen. Nyeri post section caesarea perlu penanganan yang benar dan efektif sehingga tidak menimbulkan komplikasi. Tujuan penelitian artikel, yaitu untuk mengetahui keefektifan berbagai intervensi yang dapat menurunkan skala nyeri post section caesarea. Penulisan artikel menggunakan studi literature. Pencarian data menggunakan empat data base, yaitu EBSCO, Proquest, Neliti dan Google Scholar. Kriteria artikel, yaitu berbahasa Inggris dan Indonesia, tahun terbit 2020-2021, studi penelitian menggunakan randomized control trial dan quasi experiment. Keyword dalam pencarian artikel menggunakan intervenstions AND pain AND post section caesarea. Data yang diperlukan dihimpun melalui kajian teks, kemudian dianalisis menggunakan JBI. Berdasarkan hasil studi literature menunjukan bahwa terdapat 19 artikel. Intervensi yang efektif untuk menurunkan nyeri post section caesarea, yaitu intervensi tunggal dan kombinasi. Intervensi tugal, yaitu teknik relaksasi abdomal breathing, lavender essential oil, acupuncture, terapi guided imagery, deep tissue massage, progressive muscle relaxation, latihan relaksasi benson, terapi distraksi mendengarkan music, mediasi dzikir, ekstrak lavender, pijat kaki, paket gel. Sementara itu, Intervensi kombinasi, yaitu minyak lavender dan oksigen, terapi lemon dan mozart music klasik, swedish massage dan aromaterapi lemon, teknik napas dalam dan terapi musik. Semua penelitian terbukti efektif untuk menurunkan skala nyeri post SC. Salah satu intervensi yang efektif, mudah dilakukan secara mandiri oleh ibu di rumah, aman dan tidak menimbulkan efek samping, yaitu teknik relaksasi napas dalam dengan teknik abdomal breathing, progressive muscle relaxation, relaksasi benson, mediasi dzikir dan terapi guided imagery. Namun, penelitian masih terbatas baik di luar negri maupun di Indonesia.